High Glucose Attenuates Cardioprotective Effects of Glucagon-Like Peptide-1 Through Induction of Mitochondria Dysfunction via Inhibition of β-Arrestin-Signaling - Pan, Xietian; Li, Chengxiang; Gao, Haokao (Frontiers in Physiology, 2021)
Increased vulnerability has been detected after ischemia/reperfusion injury in cardiomyocytes in diabetic patients. Glucagon-like peptide-1(GLP-1) has been proved to have notable cardioprotective effect in cardiomyocytes. However in diabetic patients the cardioprotective effects of GLP-1 is compromised, which is called GLP-1 resistance. β-arrestin is one of the two main downstream effectors of GLP-1 and β-arrestin signaling pathway exerts cardioprotective effects upon activation of GLP-1R. Our hypothesis is that increased vulnerability of cardiomyocytes in diabetic patients is partly due to disruption of β-arrestin signaling pathway. To test this, we analyzed cardiomyocyte viability and survival in high glucose and normal glucose condition after hypoxia/reoxygenation injury in vitro, additional GLP-1 was used to determine whether β-arrestin signaling pathway was involved. We also investigated the role of mitochondrial dysfunction in GLP-1 resistance. Our results showed that cardioprotective effects of GLP-1 were reduced in high glucose cultured H9C2 cells compared to normal glucose cultured H9C2, verifying the existence of GLP-1 resistance in high glucose cultured H9C2 cells. Further study suggested that β-arrestin plays a key role in GLP-1 resistance: β-arrestin expression is notably downregulated in high glucose condition and cardioprotective effects of GLP-1 can be diminished by downregulation of β-arrestin in normal glucose condition while upregulation of β-arrestin can restore cardioprotective effects of GLP-1 in high glucose condition. Then we explore how β-arrestin effects the cardioprotective effects of GLP-1 and found that β-arrestin exerts cardioprotective effects by improving mitochondria quality control via PI3K/Akt signaling pathway. Thus, our study found out a new mechanism of GLP-1 resistance of cardiomyocytes in high glucose condition that impaired β-arrestin expression caused mitochondria dysfunction and eventually cell death. Our study provided a new perspective in treating myocardial ischemia/reperfusion injury in diabetic patient.